Ultrasound based three dimensional computer aided diagnosis (CAD) tool for the diagnosis of anterior talofibular ligament - Singh, V. (Springer Verlag, 2016)
Ultrasound imaging is an investigative tool to imagine the internal organisms of human beings. Ultrasound imaging has benefits such as low cost, portability, non-ionization and real time nature. However, ultrasound imaging has limitations also like homogenous intensity regions, homogeneous textures and low contrast regions. To overcome these investigated problems, this research is developed a Computer Aided Diagnosis (CAD) system that helped in the achievement of efficient segmentation and three dimensional reconstruction of anterior talofibular ligament to enhance the diagnosis. The developed CAD system would provide the information about the input dataset, segmented results and statistical analysis of injured anterior talofibular ligament. The analysis based on the obtained results indicates the improved performance of the developed CAD system with more than 94 accurate results. In addition, this research opens new research dimensions for efficient musculoskeletal ultrasound modelling that makes it useful in clinical settings with accurate and cost effective diagnosis of anterior talofibular ligament injuries. Â© Springer International Publishing Switzerland 2016.